Dynamic Young's modulus and glass transition temperature of selected tropical wood species - Hamdan, S.; Sedik, Y.; Jusoh, Ismail; Hasan, M.; Talib, Z.A. (Maney Publishing's Online Platform, 2009)
Dynamic Young's modulus (Ed) of selected tropical wood species, namely Oyera polyphylla, Endospermum diadenum, Cratoxylum arborecens. Alstonia pneumatophora, Macaranga gig antea and Com mer sonia bartramia, used for the study was measured using the free-free flexural vibration method. Young's modulus from three point bending (E3pb) and compression parallel to grain (Ecp) was also studied. The results show that the relationship between Ed and E3Pb for all wood species is very significant with the mean value of Ed consistently larger than or sometime equal to E3pb' Surprisingly, the relationship between Ed and Ecp is not signilicant except for Alstonia pneumatophora. The dynamic mechanical thermal properties were also investigated using the dynamic mechanical thermal analyser (DMTA). The results showed that the storage modulus of the wood species at -90°C is in the range of 1·48-4·09 GPa with a glass transition temperature ranging from 50 to 70°C.